Reforms to Enhance Gender Equality in the Democratic Republic of Congo : From Advocacy to Implementation - Braunmiller, Julia Constanze (World Bank, Washington, DC, 2022)
This brief examines two successful gender equality reforms in the Democratic Republic of Congo : the introduction of the Law on Parity in 2015 and an amendment to the Family Code in 2016. These two examples highlight three success factors: gender champions across local civil society groups; government and international actors making the economic case for reforming discriminatory provisions; and international obligations that allowed the reforms to pass. These legal reforms have had demonstrably positive effects on the lives of Congolese women and society. Yet, challenges remain for the Democratic Republic of Congo to achieve full gender equality in law and practice.